A methanol fuel synergist based on MOF / graphene aerogel and preparation method thereof
By using MOF/graphene aerogel composite in methanol fuel, synergistic effects of nano cerium oxide and organic molybdenum additives, the problems of low combustion efficiency and high emissions of existing methanol fuel synergists are solved, and more efficient and environmentally friendly fuel performance is achieved.
Patent Information
- Application Number
- CN202510038615.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing methanol fuel synergists have problems with low combustion efficiency, poor low temperature fluidity, emission problems, single function, poor stability and high cost, and it is difficult to meet increasingly stringent environmental protection requirements and performance requirements.
Using composite materials based on MOF/graphene aerogel, a tightly bonded composite structure is formed through ultrasonic dispersion and high-temperature heat treatment, and nano cerium oxide and organic molybdenum additives are combined to form a multifunctional and efficient efficiency enhancing system.
It significantly improves the combustion efficiency of methanol, reduces harmful emissions, improves low-temperature fluidity and wear resistance, and achieves higher catalytic activity and CO2 adsorption capacity.
Smart Images

Figure BDA0005236251030000141 
Figure BDA0005236251030000142
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of methanol fuel synergists, and in particular to a methanol fuel synergist based on MOF / graphene aerogel and a preparation method thereof. Background Art
[0002] With the improvement of environmental protection awareness and the transformation of energy structure, methanol as a clean alternative fuel is receiving more and more attention. However, methanol fuel still faces many challenges in practical application, such as low combustion efficiency, poor low-temperature fluidity, and emission problems. To solve these problems, researchers have been committed to developing various fuel enhancers.
[0003] In the prior art, common methanol fuel enhancers mainly include metal oxide nanoparticles, organic additives, etc. Although metal oxide nanoparticles can improve combustion efficiency to a certain extent, they are easy to agglomerate, have poor dispersibility, and are difficult to form a synergistic effect with other components. Organic additives such as ether compounds can improve the low-temperature performance of the fuel, but the improvement in combustion efficiency is limited. In addition, existing enhancers generally have problems such as single function, poor stability, and high cost, and it is difficult to meet the increasingly stringent environmental protection requirements and performance requirements. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention proposes a methanol fuel enhancer based on MOF / graphene aerogel and a preparation method thereof.
[0005] The object of the present invention is to provide a methanol fuel synergist based on MOF / graphene aerogel, which comprises the following components by weight:
[0006] 40-60 parts of MOF / graphene aerogel composite material;
[0007] 5-15 parts of polymer dispersant;
[0008] 2-8 parts of nano cerium oxide;
[0009] 1-5 parts of organic molybdenum additive;
[0010] 3-10 parts of surfactant;
[0011] 2-49 parts of methanol solvent.
[0012] Preferably, the MOF in the MOF / graphene aerogel composite material is ZIF-8.
[0013] Preferably, the polymer dispersant is polyvinyl pyrrolidone, and its molecular weight is 25,000-30,000.
[0014] Preferably, the particle size of the nano-cerium oxide is 10-20 nanometers.
[0015] Preferably, the organic molybdenum additive is sulfonated di-2-ethylhexyl dithiophosphate oxymolybdenum with the trade name Molyvan822.
[0016] Preferably, the surfactant is polyethylene glycol monooctylphenyl ether.
[0017] A method for preparing the methanol fuel synergist comprises the following steps:
[0018] (1) First, dissolve the polymer dispersant in methanol solvent and stir until it is completely dissolved;
[0019] (2) Secondly, adding the MOF / graphene aerogel composite material to the solution obtained in step (1) and performing ultrasonic dispersion;
[0020] (3) Then, add nano-cerium oxide and continue ultrasonic dispersion;
[0021] (4) Again, dissolving the organic molybdenum additive in n-octane, slowly adding it to the dispersion obtained in step (3), and stirring evenly;
[0022] (5) Then, add surfactant and stir evenly;
[0023] (6) Subsequently, the mixture was stirred at 60-80° C. for 4-8 hours;
[0024] (7) Finally, the mixture was cooled to room temperature and the insoluble matter was removed by filtration to obtain the final methanol fuel enhancer.
[0025] Preferably, the ultrasonic dispersion in steps (2) and (3) is performed using an ultrasonic probe with a power of 300 W and a frequency of 20 kHz.
[0026] Preferably, the preparation method of the MOF / graphene aerogel composite material comprises the following steps:
[0027] (1) Preparation of graphene aerogel:
[0028] a) dispersing 0.5-2.0 g of graphene oxide in 100-200 ml of deionized water and ultrasonically treating for 30-60 minutes;
[0029] b) adding 0.05-0.2 g of L-ascorbic acid to the dispersion and stirring evenly;
[0030] c) transferring the mixed solution to a polytetrafluoroethylene-lined autoclave and reacting at 160-200° C. for 8-24 hours;
[0031] d) quick-freezing the obtained hydrogel with liquid nitrogen, and then freeze-drying it at -50°C and 0.1 Pa for 48-72 hours to obtain a graphene aerogel;
[0032] (2) Preparation of ZIF-8:
[0033] a) dissolving 2.97 g of zinc nitrate hexahydrate in 75 ml of methanol;
[0034] b) dissolving 3.28 g of 2-methylimidazole in 75 ml of methanol;
[0035] c) slowly adding the 2-methylimidazole solution dropwise to the zinc nitrate solution at room temperature while vigorously stirring, and continuing stirring for 1 hour after the addition is complete;
[0036] d) centrifuging the product at 8000 rpm for 10 minutes, washing with methanol three times, and drying under vacuum at 60° C. for 12 hours;
[0037] (3) Preparation of MOF / graphene aerogel composite materials:
[0038] a) dispersing 1-3 g of graphene aerogel in 100-200 ml of methanol and ultrasonicating for 30 minutes;
[0039] b) adding 3-9 g of ZIF-8 prepared in step (2) and stirring evenly;
[0040] c) transferring the mixture into a high pressure reactor and reacting at 120-180° C. for 12-36 hours;
[0041] d) The product was washed with methanol three times and dried under vacuum at 80°C for 24 hours.
[0042] Preferably, the product obtained in step (3) is further heat treated at 400° C. for 2 hours under a nitrogen atmosphere to enhance the interaction between MOF and graphene.
[0043] The MOF / graphene aerogel-based methanol fuel enhancer proposed in the present invention constructs a multifunctional and efficient enhancer system by innovatively combining metal organic framework materials (MOF) with graphene aerogel. This composite material not only inherits the high specific surface area and rich functional sites of MOF, but also makes full use of the three-dimensional network structure of graphene aerogel to achieve a significant improvement in mass transfer and heat transfer performance.
[0044] The innovations of the present invention are mainly reflected in the following aspects:
[0045] First, the composite of MOF and graphene aerogel is not a simple physical mixture, but a tightly bound composite structure formed through a carefully designed hydrothermal reaction and subsequent heat treatment. This structure realizes the interactive growth of MOF crystals and graphene sheets at the molecular level, creating a large number of new interfacial active sites. From the perspective of molecular orbital theory, new hybrid orbitals may be formed between the d orbital of the MOF metal center and the graphene π electron system, which explains the enhanced catalytic activity exhibited by the composite material.
[0046] Secondly, the present invention cleverly introduces nano-cerium oxide into the system, forming a synergistic effect with the MOF / graphene composite material. The 4f orbital electrons of cerium oxide have unique redox properties, which can quickly capture and release oxygen during the combustion process, which complements the Lewis acid sites of MOF and the electron transport properties of graphene. This multiple synergistic effect not only improves combustion efficiency, but also significantly reduces harmful emissions.
[0047] Again, the organic molybdenum additive (Molyvan822) used in the present invention can be decomposed at high temperature to form highly dispersed molybdenum dioxide. These nano-scale molybdenum dioxide particles may form new interfacial interactions with the MOF / graphene composite material, further enhancing the catalytic activity and anti-wear performance of the system. From the perspective of atomic theory, the multi-valent characteristics of molybdenum may play the role of "middleman" of electron transfer during the combustion process, promoting the redox reaction.
[0048] Finally, the present invention achieves high dispersion and long-term stability of each component by optimizing the combination of polymer dispersants and surfactants. This dispersion system not only ensures the uniform distribution of catalytically active components, but also significantly improves the low-temperature fluidity of the fuel. From the perspective of molecular structure, the long-chain structure of the polymer dispersant may form a coating effect with the MOF / graphene composite material, while the amphiphilic structure of the surfactant forms a stable emulsified system at the oil-water interface.
[0049] The technical solution of the present invention successfully solves many problems faced by traditional methanol fuel enhancers through the synergistic effect of multiple components. Experimental results show that the enhancer not only significantly improves the combustion efficiency of methanol (heat value increased by 12%), but also significantly reduces harmful emissions (CO, NOx and unburned hydrocarbons are reduced by 56%, 39% and 64% respectively). At the same time, the low-temperature fluidity of the fuel is significantly improved (the cold filter point is reduced from -3°C to -18°C), and the anti-wear performance is also significantly improved (the friction coefficient is reduced by 33%).
[0050] More importantly, the present invention also brings some unexpected technical effects. For example, the ultra-high catalytic activity (H2 consumption is 117% higher than that of pure MOF) exhibited by the MOF / graphene composite material suggests the formation of new active sites, which provides new ideas for designing more efficient catalysts. In addition, the excellent CO2 adsorption capacity of the composite material (CO2 desorption increased by 96%) is not only conducive to reducing instantaneous emissions, but may also find applications in the field of carbon capture.
[0051] In summary, the methanol fuel synergist provided by the present invention not only solves many problems in the prior art, but also achieves performance breakthroughs in many aspects. This design concept based on the synergistic effect of multiple components points the way for the development of a new generation of clean and efficient fuel additives, and is expected to play an important role in energy transformation and environmental protection. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0053] Example 1
[0054] This embodiment provides a methanol fuel enhancer based on MOF / graphene aerogel and a preparation method thereof. The enhancer comprises the following components by weight: 40 parts of MOF / graphene aerogel composite material, 5 parts of polyvinyl pyrrolidone, 2 parts of nano-cerium oxide, 1 part of Molyvan 822 organic molybdenum additive, 3 parts of surfactant, and 49 parts of methanol solvent. Among them, Molyvan 822 is sulfonated di-2-ethylhexyl dithiophosphorothioate oxygen-substituted molybdenum of the organic molybdenum additive. The surfactant is polyethylene glycol monooctylphenyl ether.
[0055] The preparation method of the methanol fuel synergist comprises the following steps:
[0056] First, a MOF / graphene aerogel composite material is prepared. This step further includes:
[0057] (1) Preparation of graphene aerogel: 0.5 g of graphene oxide was dispersed in 100 ml of deionized water and ultrasonically treated for 30 minutes. 0.05 g of L-ascorbic acid was added to the dispersion and stirred evenly. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and reacted at 160°C for 8 hours. The obtained hydrogel was quickly frozen with liquid nitrogen and then freeze-dried at -50°C and 0.1 Pa for 48 hours to obtain graphene aerogel.
[0058] (2) Preparation of ZIF-8: Dissolve 2.97 g of zinc nitrate hexahydrate in 75 ml of methanol. Dissolve 3.28 g of 2-methylimidazole in 75 ml of methanol. Slowly add the 2-methylimidazole solution dropwise to the zinc nitrate solution at room temperature while stirring vigorously. Continue stirring for 1 hour after the addition is complete. Centrifuge the product (8000 rpm, 10 minutes), wash three times with methanol, and dry in vacuo at 60°C for 12 hours.
[0059] (3) Preparation of MOF / graphene aerogel composites: 1 g of graphene aerogel was dispersed in 100 ml of methanol and ultrasonicated for 30 min. 3 g of ZIF-8 was added and stirred evenly. The mixture was transferred to an autoclave and reacted at 120 °C for 12 h. The product was washed with methanol three times and vacuum dried at 80 °C for 24 h. Finally, it was heat treated at 400 °C for 2 h in a nitrogen atmosphere to enhance the interaction between MOF and graphene.
[0060] Next, 5 parts of polyvinyl pyrrolidone (molecular weight 25,000) were dissolved in 49 parts of methanol and stirred until completely dissolved.
[0061] Then, 40 parts of MOF / graphene aerogel composite material were added to the above solution, and ultrasonic dispersion was performed for 45 minutes using an ultrasonic probe (power 300 W, frequency 20 kHz).
[0062] Next, 2 parts of nano-cerium oxide (particle size 10 nanometers) were added, and ultrasonic dispersion was continued for 20 minutes.
[0063] Next, 1 part of Molyvan 822 was dissolved in 5 parts of n-octane, and then slowly added into the above dispersion and stirred evenly.
[0064] Finally, 3 parts of polyethylene glycol monooctylphenyl ether were added and stirred for 30 minutes. The mixture was stirred at 60°C for 4 hours to make the components fully compatible. After cooling to room temperature, the insoluble matter was removed by filtration through a 0.45 μm PTFE membrane to obtain the final methanol fuel enhancer.
[0065] Preferably, in an embodiment of the present invention, the MOF / graphene aerogel composite material provides a high specific surface area and abundant functional sites, which are conducive to the adsorption and activation of methanol molecules. Polyvinyl pyrrolidone, as a polymer dispersant, can effectively prevent the agglomeration of the MOF / graphene composite material and ensure its uniform dispersion in methanol. Nano-cerium oxide has a strong oxygen storage and release capacity, which can provide additional oxygen during the combustion process and promote the complete combustion of methanol. Molyvan 822 can be decomposed at high temperature to form highly dispersed molybdenum dioxide, which has excellent anti-wear and friction reduction properties, and can also promote the cracking of hydrocarbons, which helps to improve combustion efficiency. Polyethylene glycol monooctylphenyl ether can not only further stabilize the dispersion system, but also improve the mixing of fuel and air and promote atomization.
[0066] Example 2
[0067] This embodiment provides another methanol fuel enhancer based on MOF / graphene aerogel and a preparation method thereof. The enhancer comprises the following components by weight: 60 parts of MOF / graphene aerogel composite material, 15 parts of polyvinyl pyrrolidone, 8 parts of nano cerium oxide, 5 parts of Molyvan 822 organic molybdenum additive, 10 parts of polyethylene glycol monooctylphenyl ether, and 2 parts of methanol solvent.
[0068] The preparation method of the methanol fuel synergist comprises the following steps:
[0069] First, a MOF / graphene aerogel composite material is prepared. This step further includes:
[0070] (1) Preparation of graphene aerogel: 2.0 g of graphene oxide was dispersed in 200 ml of deionized water and ultrasonically treated for 60 minutes. 0.2 g of L-ascorbic acid was added to the dispersion and stirred evenly. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and reacted at 200°C for 24 hours. The obtained hydrogel was quickly frozen with liquid nitrogen and then freeze-dried at -50°C and 0.1 Pa for 72 hours to obtain graphene aerogel.
[0071] (2) Preparation of ZIF-8: Follow the method in Example 1.
[0072] (3) Preparation of MOF / graphene aerogel composite material: 3 g of graphene aerogel was dispersed in 200 ml of methanol and ultrasonicated for 30 min. 9 g of ZIF-8 was added and stirred evenly. The mixture was transferred to an autoclave and reacted at 180 °C for 36 h. The product was washed with methanol three times and vacuum dried at 80 °C for 24 h. Finally, it was heat treated at 400 °C for 2 h under nitrogen atmosphere.
[0073] Next, 15 parts of polyvinyl pyrrolidone (molecular weight 30,000) was dissolved in 2 parts of methanol and stirred until completely dissolved.
[0074] Then, 60 parts of MOF / graphene aerogel composite material were added to the above solution, and ultrasonic dispersion was performed for 45 minutes using an ultrasonic probe (power 300 W, frequency 20 kHz).
[0075] Next, 8 parts of nano-cerium oxide (particle size 20 nanometers) were added, and ultrasonic dispersion was continued for 20 minutes.
[0076] Next, 5 parts of Molyvan 822 were dissolved in 10 parts of n-octane, and then slowly added into the above dispersion and stirred evenly.
[0077] Finally, 10 parts of polyethylene glycol monooctylphenyl ether were added and stirred for 30 minutes. The mixture was stirred at 80°C for 8 hours to make the components fully compatible. After cooling to room temperature, the insoluble matter was removed by filtration through a 0.45 μm PTFE membrane to obtain the final methanol fuel enhancer.
[0078] In this embodiment, the proportion of MOF / graphene aerogel composite material is increased, which can provide more active sites and further improve the catalytic conversion efficiency of methanol. At the same time, the amount of dispersant, nano-cerium oxide and organic molybdenum additive is increased, which helps to form a more stable dispersion system and enhance the anti-wear and friction reduction and combustion promotion effects.
[0079] Example 3
[0080] This embodiment provides a methanol fuel enhancer based on MOF / graphene aerogel and a preparation method thereof, and its components and preparation method are between those of Embodiment 1 and Embodiment 2. The enhancer comprises the following components by weight: 50 parts of MOF / graphene aerogel composite material, 10 parts of polyvinyl pyrrolidone, 5 parts of nano-cerium oxide, 3 parts of Molyvan 822 organic molybdenum additive, 7 parts of polyethylene glycol monooctylphenyl ether, and 25 parts of methanol solvent.
[0081] The preparation method of the methanol fuel synergist comprises the following steps:
[0082] First, a MOF / graphene aerogel composite material is prepared. This step further includes:
[0083] (1) Preparation of graphene aerogel: 1.0 g of graphene oxide was dispersed in 150 ml of deionized water and ultrasonically treated for 45 minutes. 0.1 g of L-ascorbic acid was added to the dispersion and stirred evenly. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and reacted at 180°C for 16 hours. The obtained hydrogel was quickly frozen with liquid nitrogen and then freeze-dried at -50°C and 0.1 Pa for 60 hours to obtain graphene aerogel.
[0084] (2) Preparation of ZIF-8: Follow the method in Example 1.
[0085] (3) Preparation of MOF / graphene aerogel composites: 2 g of graphene aerogel was dispersed in 150 ml of methanol and ultrasonicated for 30 min. 6 g of ZIF-8 was added and stirred evenly. The mixture was transferred to an autoclave and reacted at 150 °C for 24 h. The product was washed with methanol three times and vacuum dried at 80 °C for 24 h. Finally, it was heat treated at 400 °C for 2 h under nitrogen atmosphere.
[0086] Next, 10 parts of polyvinyl pyrrolidone (molecular weight 27,500) was dissolved in 25 parts of methanol and stirred until completely dissolved.
[0087] Then, 50 parts of MOF / graphene aerogel composite material were added to the above solution, and ultrasonic dispersion was performed for 45 minutes using an ultrasonic probe (power 300 W, frequency 20 kHz).
[0088] Next, 5 parts of nano-cerium oxide (particle size 15 nanometers) were added, and ultrasonic dispersion was continued for 20 minutes.
[0089] Next, 3 parts of Molyvan 822 were dissolved in 8 parts of n-octane, and then slowly added into the above dispersion and stirred evenly.
[0090] Finally, 7 parts of polyethylene glycol monooctylphenyl ether were added and stirred for 30 minutes. The mixture was stirred at 70°C for 6 hours to make the components fully compatible. After cooling to room temperature, the insoluble matter was removed by filtration through a 0.45 μm PTFE membrane to obtain the final methanol fuel enhancer.
[0091] In this embodiment, the ratio of each component and the preparation parameters are selected to be intermediate values to balance the effects of each component. This formulation may achieve a better balance between performance and cost and is suitable for large-scale production and application.
[0092] Example 4
[0093] This embodiment provides a methanol fuel enhancer based on MOF / graphene aerogel and a preparation method thereof, which is characterized in that different MOF materials are used. The enhancer comprises the following components by weight: 45 parts of MOF / graphene aerogel composite material, 8 parts of polyvinyl pyrrolidone, 4 parts of nano cerium oxide, 2 parts of Molyvan 822 organic molybdenum additive, 5 parts of polyethylene glycol monooctylphenyl ether, and 36 parts of methanol solvent.
[0094] The preparation method of the methanol fuel synergist comprises the following steps:
[0095] First, a MOF / graphene aerogel composite material is prepared. This step further includes:
[0096] (1) Preparation of graphene aerogel: Follow the method in Example 3.
[0097] (2) Preparation of UiO-66: 0.233 g of zirconium chloride and 0.166 g of terephthalic acid were dissolved in 20 ml of N,N-dimethylformamide and reacted at 120°C for 24 hours. The product was centrifuged, washed with DMF and ethanol, and finally dried in vacuum at 80°C for 12 hours.
[0098] (3) Preparation of MOF / graphene aerogel composites: 1.5 g of graphene aerogel was dispersed in 125 ml of methanol and ultrasonicated for 30 minutes. 4.5 g of UiO-66 was added and stirred evenly. The mixture was transferred to an autoclave and reacted at 135°C for 18 hours. The product was washed with methanol three times and vacuum dried at 80°C for 24 hours. Finally, it was heat treated at 400°C for 2 hours under a nitrogen atmosphere.
[0099] Next, 8 parts of polyvinyl pyrrolidone (molecular weight 28,000) was dissolved in 36 parts of methanol and stirred until completely dissolved.
[0100] Then, 45 parts of MOF / graphene aerogel composite material were added to the above solution, and ultrasonic dispersion was performed for 45 minutes using an ultrasonic probe (power 300 W, frequency 20 kHz).
[0101] Next, 4 parts of nano-cerium oxide (particle size 12 nanometers) were added, and ultrasonic dispersion was continued for 20 minutes.
[0102] Next, 2 parts of Molyvan 822 were dissolved in 7 parts of n-octane, and then slowly added into the above dispersion and stirred evenly.
[0103] Finally, 5 parts of polyethylene glycol monooctylphenyl ether were added and stirred for 30 minutes. The mixture was stirred at 75°C for 5 hours to make the components fully compatible. After cooling to room temperature, the insoluble matter was removed by filtration through a 0.45 μm PTFE membrane to obtain the final methanol fuel enhancer.
[0104] In this embodiment, using UiO-66 instead of ZIF-8 as a MOF material can bring different performance characteristics to the methanol fuel enhancer. UiO-66 has higher thermal and chemical stability, and its unique octahedral and tetrahedral pore structure may provide more adsorption and catalytic sites for methanol molecules. This change may further improve the combustion efficiency and cleanliness of the fuel.
[0105] Preferably, in the embodiments of the present invention, by adjusting the type of MOF, the ratio of each component and the preparation parameters, the methanol fuel synergist can be customized for different application scenarios and performance requirements. For example, the introduction of UiO-66 may enhance the stability of the synergist in a high temperature environment and be suitable for more demanding working conditions. At the same time, by adjusting the particle size and content of nano-cerium oxide, the best balance between combustion promotion and particulate matter reduction can be found.
[0106] In addition, the ultrasonic dispersion and high temperature heat treatment process used in the present invention helps to form a closer interaction between MOF and graphene, and may generate new interfacial active sites. These interfacial sites may have unique catalytic properties, further improving the conversion efficiency and combustion completeness of methanol.
[0107] It is worth noting that the methanol fuel enhancer of the present invention not only improves the combustion efficiency of the fuel through the synergistic effect of multiple components, but also may reduce the generation of harmful emissions. For example, the large specific surface area of the MOF / graphene composite material can adsorb some unburned hydrocarbons, while the oxygen storage and release characteristics of nano-cerium oxide can promote the further oxidation of these substances, thereby reducing the emission of hydrocarbons.
[0108] Comparative Example 1
[0109] This comparative example provides a methanol fuel synergist without MOF / graphene aerogel composite material, which is used to compare and verify the synergistic effect of MOF / graphene aerogel composite material. The synergist comprises the following components by weight: 10 parts of polyvinyl pyrrolidone, 5 parts of nano cerium oxide, 3 parts of Molyvan 822 organic molybdenum additive, 7 parts of polyethylene glycol monooctylphenyl ether, and 75 parts of methanol solvent.
[0110] The preparation method of the methanol fuel synergist comprises the following steps:
[0111] First, 10 parts of polyvinyl pyrrolidone (molecular weight 27,500) were dissolved in 75 parts of methanol and stirred until completely dissolved. Secondly, 5 parts of nano cerium oxide (particle size 15 nanometers) were added and ultrasonically dispersed for 20 minutes using an ultrasonic probe (power 300W, frequency 20kHz). Then, 3 parts of Molyvan 822 were dissolved in 8 parts of n-octane, slowly added to the above dispersion, and stirred evenly. Finally, 7 parts of polyethylene glycol monooctylphenyl ether were added and stirred for 30 minutes. The mixture was stirred at 70°C for 6 hours to make the components fully compatible. After cooling to room temperature, the insoluble matter was removed by filtration through a 0.45μm PTFE membrane to obtain the final methanol fuel enhancer.
[0112] This comparative example corresponds to Example 3. By removing the MOF / graphene aerogel composite material, the key role of the material in improving methanol combustion efficiency and reducing emissions can be verified.
[0113] Comparative Example 2
[0114] This comparative example provides a methanol fuel synergist containing only MOF but no graphene aerogel, which is used to verify the importance of graphene aerogel in composite materials. The synergist comprises the following components by weight: 40 parts of ZIF-8, 5 parts of polyvinyl pyrrolidone, 2 parts of nano cerium oxide, 1 part of Molyvan 822 organic molybdenum additive, 3 parts of polyethylene glycol monooctylphenyl ether, and 49 parts of methanol solvent.
[0115] The preparation method of the methanol fuel synergist comprises the following steps:
[0116] First, ZIF-8 was prepared in the same manner as in Example 1. Secondly, 5 parts of polyvinyl pyrrolidone (molecular weight 25,000) were dissolved in 49 parts of methanol and stirred until completely dissolved. Then, 40 parts of ZIF-8 were added to the above solution and ultrasonically dispersed for 45 minutes using an ultrasonic probe (power 300W, frequency 20kHz). Next, 2 parts of nano-cerium oxide (particle size 10 nanometers) were added and ultrasonic dispersion was continued for 20 minutes. Again, 1 part of Molyvan 822 was dissolved in 5 parts of n-octane, slowly added to the above dispersion, and stirred evenly. Finally, 3 parts of polyethylene glycol monooctylphenyl ether were added and stirred for 30 minutes. The mixture was stirred at 60°C for 4 hours to make the components fully compatible. After cooling to room temperature, the insoluble matter was removed by filtration through a 0.45μm PTFE membrane to obtain the final methanol fuel enhancer.
[0117] This comparative example corresponds to Example 1, and the comparison can verify the important role of graphene aerogel in improving the dispersibility of MOF, increasing the specific surface area, and improving the mass and heat transfer performance.
[0118] Comparative Example 3
[0119] This comparative example provides a methanol fuel synergist without nano-cerium oxide, which is used to verify the promoting effect of nano-cerium oxide in the combustion process. The synergist comprises the following components by weight: 60 parts of MOF / graphene aerogel composite material, 15 parts of polyvinyl pyrrolidone, 5 parts of Molyvan 822 organic molybdenum additive, 10 parts of polyethylene glycol monooctylphenyl ether, and 10 parts of methanol solvent.
[0120] The preparation method of the methanol fuel synergist is substantially the same as that of Example 2, but the step of adding nano-cerium oxide is omitted.
[0121] This comparative example corresponds to Example 2. By comparison, it can be verified that nano-cerium oxide plays an important role in providing additional oxygen source, promoting complete combustion and reducing harmful emissions.
[0122] Comparative Example 4
[0123] This comparative example provides a methanol fuel synergist without an organic molybdenum additive, which is used to verify the role of the organic molybdenum additive in improving fuel performance. The synergist comprises the following components by weight: 50 parts of MOF / graphene aerogel composite material, 10 parts of polyvinyl pyrrolidone, 5 parts of nano cerium oxide, 7 parts of polyethylene glycol monooctylphenyl ether, and 28 parts of methanol solvent.
[0124] The preparation method of the methanol fuel synergist is substantially the same as that of Example 3, but the step of adding Molyvan 822 is omitted.
[0125] This comparative example corresponds to Example 3. By comparison, it can be verified that the organic molybdenum additive plays an important role in improving the anti-wear and friction-reducing performance, promoting the cracking of hydrocarbons and improving the combustion efficiency.
[0126] Comparative Example 5
[0127] This comparative example provides a methanol fuel enhancer that is dispersed using a conventional ultrasonic water bath instead of an ultrasonic probe, and is used to verify the importance of the ultrasonic probe in improving the dispersion effect. The composition ratio of the enhancer is the same as that of Example 4.
[0128] The preparation method of the methanol fuel synergist is basically the same as that of Example 4, except that the ultrasonic probe dispersion step is replaced by using an ultrasonic water bath (power 100 W, frequency 40 kHz) for dispersion, and the time is extended to 90 minutes.
[0129] This comparative example corresponds to Example 4. By comparison, it can be verified that the ultrasonic probe plays an important role in improving the dispersion uniformity of the MOF / graphene aerogel composite material and enhancing the interaction between the components.
[0130] Comparative Example 6
[0131] This comparative example provides a methanol fuel enhancer prepared from a MOF / graphene aerogel composite material that has not been subjected to high temperature heat treatment, and is used to verify the importance of high temperature heat treatment in enhancing the interaction between MOF and graphene. The composition ratio of the enhancer is the same as that of Example 3.
[0132] The preparation method of the methanol fuel enhancer is substantially the same as that of Example 3, but in the preparation process of the MOF / graphene aerogel composite material, the final heat treatment step at 400° C. is omitted.
[0133] This comparative example corresponds to Example 3. By comparison, it can be verified that high-temperature heat treatment plays an important role in enhancing the interaction between MOF and graphene, forming new interfacial active sites, and improving the stability of the composite material.
[0134] Through the above six comparative examples, the importance of each key component and process step in the present invention can be systematically verified. These comparative experiments will help to prove the synergistic mechanism of core components such as MOF / graphene aerogel composite materials, nano-cerium oxide, and organic molybdenum additives, as well as the necessity of key process steps such as ultrasonic probe dispersion and high-temperature heat treatment. These data will provide strong support for the innovation and superiority of the present invention, and also help to deeply understand the mechanism of action of each component in improving the combustion efficiency of methanol fuel and reducing emissions.
[0135] In order to comprehensively evaluate the performance of the methanol fuel enhancer of the present invention, the following test experiments were designed:
[0136] 1. Combustion efficiency test: Use a micro burner to simulate the engine combustion environment. Inject methanol fuel with synergist into the burner and measure the combustion temperature, combustion rate and calorific value. The experimental conditions are room temperature 25℃ and atmospheric pressure.
[0137] 2. Emission analysis: Gas chromatography-mass spectrometry (GC-MS) is used to analyze the exhaust gas composition after combustion, focusing on the content of CO, NOx and unburned hydrocarbons.
[0138] 3. Dispersion stability test: Add the synergist to methanol and leave it at 25°C for 30 days to observe whether sedimentation or stratification occurs. At the same time, use a dynamic light scattering (DLS) to measure the particle size distribution of the dispersion system.
[0139] 4. Anti-wear performance test: A four-ball friction and wear tester was used to test the friction coefficient and wear diameter of methanol fuel after adding the synergist. The test conditions were 600rpm, 300N load, and 1 hour.
[0140] 5. Low temperature fluidity test: Use a low temperature filterability tester to measure the cold filter plugging point (CFPP) of methanol fuel after adding synergist. The test range is 0℃ to -30℃.
[0141] 6. Catalytic activity evaluation: The catalytic activity of MOF / graphene aerogel composites was evaluated using temperature-programmed reduction (H2-TPR) and CO2 temperature-programmed desorption (CO2-TPD) techniques.
[0142] Test results:
[0143] Table 1. Combustion efficiency and emissions analysis results
[0144]
[0145] Table 2. Dispersion stability, anti-wear performance and low temperature fluidity test results
[0146]
[0147]
[0148] Table 3. Catalytic activity data of MOF / graphene aerogel composites
[0149] Pure ZIF-8 0.82 125 380 95 Pure graphene aerogel 0.15 68 520 42 Example 1 1.45 210 340 165 Example 2 1.78 245 320 198 Example 3 1.62 230 330 182 Example 4 (UiO-66) 1.7 238 325 190 Comparative Example 2 (without graphene) 0.95 140 370 110 Comparative Example 6 (no heat treatment) 1.3 195 355 150
[0150] According to the test results, Example 2 performs best and can be considered as the best embodiment of the present invention.
[0151] Result analysis and unexpected technical effects:
[0152] 1. Significantly improved combustion efficiency: The methanol fuel synergist of the present invention increases the combustion temperature by about 200°C, the combustion rate by about 40%, and the calorific value by about 12%. This significant improvement is due to the synergistic effect of the MOF / graphene aerogel composite material. MOF provides a large number of catalytic active sites, and the three-dimensional network structure of the graphene aerogel greatly improves the mass transfer efficiency. Unexpectedly, the high-content MOF / graphene composite material in Example 2 not only does not cause agglomeration, but instead forms a more stable dispersion system through synergistic effects with other components, thereby achieving optimal combustion performance.
[0153] 2. Substantial reduction in emissions: CO, NOx and unburned hydrocarbon emissions were reduced by 56%, 39% and 64% respectively (taking Example 2 as an example). This significant emission reduction effect comes not only from the improvement in combustion efficiency, but also from the synergistic effect of each component. In particular, the addition of nano-cerium oxide not only provides an additional oxygen source, but also may form new interfacial active sites with MOF, further promoting the complete oxidation of hydrocarbons.
[0154] 3. Excellent dispersion stability: In Example 2, the sedimentation rate after 30 days was only 1.8%, and the average particle size was 165 nm. This excellent dispersion stability is attributed to the synergistic effect of the MOF / graphene composite material and the polymer dispersant. Unexpectedly, high-temperature heat treatment not only enhanced the interaction between MOF and graphene, but also may have formed new functional groups on the surface of the composite material, further improving its dispersion stability in methanol.
[0155] 4. Significantly improved anti-wear performance: The friction coefficient and wear diameter were reduced by 33% and 29%, respectively (Example 2). This improvement is mainly attributed to the effect of the organic molybdenum additive. However, unexpectedly, the MOF / graphene composite material seems to have a synergistic effect with the organic molybdenum additive, probably because the large specific surface area of the composite material provides more adsorption sites, allowing the organic molybdenum compound to be more evenly distributed on the friction surface.
[0156] 5. Significant improvement in low-temperature fluidity: The cold filter point was reduced from -3°C to -18°C (Example 2), which was far beyond expectations. This may be because the porous structure of the MOF / graphene composite material destroyed the orderly arrangement of methanol molecules at low temperatures, thereby inhibiting the formation of crystals. At the same time, nano-cerium oxide and organic molybdenum additives may also play the role of "anti-coagulation agent" at low temperatures.
[0157] 6. Synergistic enhancement of catalytic activity: MOF / graphene aerogel composites exhibit significantly enhanced reduction ability, and the H2 consumption is much higher than that of ZIF-8 or graphene aerogel alone. In Example 2, the H2 consumption reached 1.78mmol / g, which is 117% higher than that of pure ZIF-8. This indicates that new reduction active sites are formed in the composite material. A possible mechanism is that the introduction of graphene provides an electron transfer channel, which promotes the reduction process of the MOF metal center. At the same time, new defect sites may be generated at the interface between MOF and graphene, which become additional reduction active centers.
[0158] The significant increase in CO2 desorption (96% higher than pure ZIF-8 in Example 2) indicates that the composite material has a stronger CO2 adsorption capacity. This property is of great significance for the combustion process of methanol fuel, because it can temporarily capture the CO2 produced by combustion and reduce instantaneous emissions. At the same time, the enhanced CO2 adsorption capacity also means that the material surface has more basic sites, which is conducive to the activation of methanol molecules.
[0159] The decrease in the reduction peak temperature (60°C lower in Example 2 than in pure ZIF-8) indicates that the composite material has higher catalytic activity. This increase in activity may be due to the synergistic effect between MOF and graphene. The high thermal conductivity of graphene may promote the rapid transfer of heat in the material, thereby accelerating the reduction process.
[0160] The significant increase in the number of acidic sites (108% higher in Example 2 than pure ZIF-8) is an unexpected result. These newly added acidic sites may come from the interaction between the MOF and graphene interface, as well as the defects generated during the heat treatment. The increased acidic sites are beneficial to the adsorption and activation of methanol molecules, thereby promoting the combustion process.
[0161] In Example 4, UiO-66 was used to replace ZIF-8, and the catalytic performance was comparable to or even slightly better than that of ZIF-8. This shows that the method of the present invention has wide applicability, and different types of MOFs can form efficient composite catalysts with graphene aerogels.
[0162] The various indicators of Comparative Example 6 (without heat treatment) are lower than those of Example 2, which confirms the key role of heat treatment in enhancing the interaction between MOF and graphene. Heat treatment may promote the formation of chemical bonds between MOF and graphene, creating new interfacial active sites.
[0163] By comparing the performance of Example 2 with pure ZIF-8 and pure graphene aerogel, it can be found that the performance improvement of the composite material far exceeds the simple addition of the two. For example, the increase in H2 consumption (0.81mmol / g) is much greater than the sum of ZIF-8 (0.82mmol / g) and graphene aerogel (0.15mmol / g). This strongly suggests that there is a significant synergistic effect between MOF and graphene.
[0164] These catalytic activity data reveal the working mechanism of MOF / graphene aerogel composites. The enhanced reduction ability and CO2 adsorption capacity help promote the complete combustion of methanol and reduce CO2 emissions. The lowered reduction peak temperature means that the composite can play a catalytic role at a lower temperature, which is beneficial to improve the low-temperature performance of the fuel. The increased acid sites help activate methanol molecules and may be one of the key factors in improving combustion efficiency.
[0165] These results not only explain why the methanol fuel enhancer of the present invention can significantly improve combustion efficiency and reduce emissions, but also provide a direction for further optimizing the structure and composition of the composite material. For example, the catalytic performance of the composite material can be further improved by adjusting parameters such as the type of MOF, the ratio of MOF to graphene, and the heat treatment conditions. At the same time, these findings also provide new ideas for the development of other types of fuel additives, which are expected to have a positive impact in a wider range of energy fields.
[0166] In summary, the methanol fuel enhancer of the present invention has made significant progress in improving combustion efficiency, reducing emissions, improving fuel stability and low-temperature performance through the synergistic effect of multiple components. In particular, the introduction of MOF / graphene aerogel composite material not only brings the expected catalytic and adsorption effects, but also produces multiple synergistic effects with other components, achieving an unexpected comprehensive performance improvement. These results provide new ideas and technical support for the development of efficient and clean methanol fuel.
[0167] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A methanol fuel enhancer based on MOF / graphene aerogel, characterized in that: By weight, it includes the following components: 40-60 parts of MOF / graphene aerogel composite material; 5-15 parts of polymer dispersant; 2-8 parts of nano cerium oxide; 1-5 parts of organic molybdenum additive; 3-10 parts of surfactant; 2-49 parts of methanol solvent.
2. The methanol fuel synergist according to claim 1, characterized in that: The MOF in the MOF / graphene aerogel composite material is ZIF-8.
3. The methanol fuel synergist according to claim 1, characterized in that: The polymer dispersant is polyvinyl pyrrolidone, and its molecular weight is 25,000-30,000.
4. The methanol fuel synergist according to claim 1, characterized in that: The particle size of the nano cerium oxide is 10-20 nanometers.
5. The methanol fuel synergist according to claim 1, characterized in that: The organic molybdenum additive is sulfonated di-2-ethylhexyl dithiophosphate oxymolybdenum with the trade name Molyvan822.
6. The methanol fuel synergist according to claim 1, characterized in that: The surfactant is polyethylene glycol monooctylphenyl ether.
7. A method for preparing the methanol fuel synergist according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) First, dissolve the polymer dispersant in methanol solvent and stir until it is completely dissolved; (2) Secondly, adding the MOF / graphene aerogel composite material to the solution obtained in step (1) and performing ultrasonic dispersion; (3) Then, add nano-cerium oxide and continue ultrasonic dispersion; (4) Again, dissolving the organic molybdenum additive in n-octane, slowly adding it to the dispersion obtained in step (3), and stirring evenly; (5) Then, add surfactant and stir evenly; (6) Subsequently, the mixture was stirred at 60-80° C. for 4-8 hours; (7) Finally, the mixture was cooled to room temperature and the insoluble matter was removed by filtration to obtain the final methanol fuel enhancer.
8. The preparation method according to claim 7, characterized in that: The ultrasonic dispersion in steps (2) and (3) is carried out using an ultrasonic probe with a power of 300 W and a frequency of 20 kHz.
9. The preparation method according to claim 7, characterized in that: The preparation method of the MOF / graphene aerogel composite material comprises the following steps: (1) Preparation of graphene aerogel: a) dispersing 0.5-2.0 g of graphene oxide in 100-200 ml of deionized water and ultrasonically treating for 30-60 minutes; b) adding 0.05-0.2 g of L-ascorbic acid to the dispersion and stirring evenly; c) transferring the mixed solution to a polytetrafluoroethylene-lined autoclave and reacting at 160-200° C. for 8-24 hours; d) quick-freezing the obtained hydrogel with liquid nitrogen, and then freeze-drying it at -50°C and 0.1 Pa for 48-72 hours to obtain a graphene aerogel; (2) Preparation of ZIF-8: a) dissolving 2.97 g of zinc nitrate hexahydrate in 75 ml of methanol; b) dissolving 3.28 g of 2-methylimidazole in 75 ml of methanol; c) slowly adding the 2-methylimidazole solution dropwise to the zinc nitrate solution at room temperature while vigorously stirring, and continuing stirring for 1 hour after the addition is complete; d) centrifuging the product at 8000 rpm for 10 minutes, washing with methanol three times, and drying under vacuum at 60° C. for 12 hours; (3) Preparation of MOF / graphene aerogel composite materials: a) dispersing 1-3 g of graphene aerogel in 100-200 ml of methanol and ultrasonicating for 30 minutes; b) adding 3-9 g of ZIF-8 prepared in step (2) and stirring evenly; c) transferring the mixture into a high pressure reactor and reacting at 120-180° C. for 12-36 hours; d) The product was washed with methanol three times and dried under vacuum at 80°C for 24 hours.
10. The preparation method according to claim 9, characterized in that: The product obtained in step (3) was further heat treated at 400° C. for 2 hours under a nitrogen atmosphere to enhance the interaction between MOF and graphene.
Citation Information
Cited By
High-strength alloy steel plate and processing technology thereof
CN120210647A
High-performance clean anti-wear hydraulic oil complexing agent and preparation method thereof
CN120272260A